THE LITERARY TEXT AS A TRANSLATOR OF THE SEMANTICS OF THE CONCEPT - Varvaruk, Inna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
The article examines the functioning of the literary text as a translator of the semantics of the concept within the cognitive-linguistic paradigm. The relationship between the conceptual and linguistic pictures of the world is analyzed, and the role of the concept as a mental unit structuring the content of a literary text is determined. The study substantiates the correlation between concept and text, where the concept is interpreted as a deep semantic structure that reflects the author’s intentions and directs the process of text perception by the recipient. Particular attention is paid to the literary concept as a specific cognitive unit of the individual author’s worldview, characterized by associativity, symbolism, emotional and expressive markedness, and semantic dynamism. The article outlines the differences between cognitive and literary concepts and identifies the structural components of a literary concept as well as the features of its verbalization in the text. Special emphasis is placed on the associative and figurative potential of the literary concept in modeling the author’s picture of the world. The concept of «laughter» is also considered as one of the dominant elements of the emotive picture of the world in contemporary literary discourse.